Exploration of Children’s Literature about Middle Eastern Nations and Islamic Culture - Junko Sakoi (WOW Stories, 2021)
Building off of the belief that children's literature can support students in (re)discovering cultures in the Middle East, the TUSD literacy community was formed to help teachers become more confident about covering the Middle East in lessons. Children's literature also helped develop critical lenses and gain an authentic intercultural understanding of the Middle East—rethinking the social attitudes associated with a warzone context. The methods used to help familiarize teachers with these subjects and prepare them for teaching classes with these books included: expanding teachers' knowledge of literature, developing paired books and text sets, and having book discussions and literacy engagements.